ANALISA PROSES PENGELASAN GESEK PADA PENYAMBUNGAN BAJA AISI 1010 DAN AISI 1050 DENGAN VARIASI WAKTU DAN PUTARAN SPINDEL MENGGUNAKAN MESIN BUBUT - Andana, Himawan D; Hermawan, Yuni; Sakura, Rahma Rei; Trifiananto, Muhammad; Hentihu, M Fahrur Rozy (STATOR: Jurnal Ilmiah Teknik Mesin, 2023)
The development of the welding process in the current era is growing, especially in terms of components of building construction tools and machines. Friction welding is included in the type (solid state) or without filler metal (filler) in the process, the compressive force can be utilized from the friction obtained between the two workpieces to carry out the joining process. Friction welding is a solution to overcome problems that are difficult to solve using fusion welding, friction welding can be applied to two dissimilar metals while other welding methods are almost impossible. The purpose of this study was to analyze the friction welding process on AISI 1010 and AISI 1050 steel joints with variations in welding time and spindle rotation using a lathe. The combination of independent variables that can produce the highest tensile test value, namely spindle rotation of 1170 rpm and 50 seconds of welding time can produce a tensile test value of 42.55 kgf/mm2. Meanwhile, the combination of independent variables that produced the lowest tensile test value was the spindle rotation of 900 rpm and 70 seconds of welding time, namely 30.14 kgf/mm2. The most significant independent variable is spindle rotation with 80%.